The Effectiveness of the Teams Games Tournament Cooperative Learning Strategies in Qira'ah Jahriyah | faʿāliyat istikhdām istirātījiyyat al-taʿallum al-taʿāwunī binawʿ jawlāt ʾalʿāb al-farīq fī tadrīs al-qirāʾah al-jahriyyah - Wahyuni, Ade Sri; Arifin, Zainul; Rahmawati, Rahmawati (Institut Agama Islam Negeri Palangka Raya, 2024)
Learning strategies are one of the key components in the teaching and learning process. Numerous studies have stated that the Teams Games Tournament (TGT), which is a part of cooperative learning strategies, has proven effective in improving student learning outcomes. However, its application in teaching Qira'ah Jahriyah (reading aloud) has not been widely explored. Therefore, researchers conducted a study at MTs.S Pondok Pesantren Al-Muttaqin Balai Belo Agam to determine the effectiveness of the TGT strategy in learning Qira'ah Jahriyah. The research employed a quantitative approach with experimental methods and utilized a Quasi-Experimental Design with purposive sampling. The sample consisted of 8th-grade students divided into two classes. Data collection was conducted using tests, and data analysis was performed using the t-test in SPSS 22. In the experimental class, the minimum posttest score was 75 and the maximum was 95, with a mean of 83.21. In the control class, the minimum score was 60 and the maximum was 85, with a mean of 73.57. The results showed that the t-test, Sig (2-tailed) 0.000 < 0.05, indicating a significant influence of the TGT cooperative learning strategy on the Qira'ah Jahriyah learning outcomes of 8th-grade students at MTs.S Al-Muttaqin Islamic Boarding School, Balai Belo Agam.